The impact of metal waste imports on industrial wastewater discharge in China - Chen, Weitao; Yan, Weitao (Frontiers in Environmental Science, 2022)
Once the world’s largest waste importer, China alleviated the shortage of raw materials in its related industries; however, such activity incited more prominent ecological and environmental problems. Based on several major sample databases from 2003 to 2006—including the China Industry Business Performance Data, Customs Trade Database, and scrap metal commodity data from Harmonized System code catalogues—this paper establishes a city-level panel data model and a mediation effect model to examine the impact of scrap metal imports on industrial wastewater discharge in China as well as the mechanism of this impact. Furthermore, this paper analyses the impact of scrap metal imports on Chinese enterprises’ pollution fees from the perspective of enterprises to ensure the robustness of results based on the China Industry Business Performance Data in 2004. Results show that scrap metal imports significantly increase industrial wastewater discharge in China and exacerbate environmental pollution. Specifically, results indicate that if scrap metal imports increase by 1%, wastewater discharge will significantly increase by approximately 0.015–0.198 percentage points. In terms of the impact mechanisms, by driving the development of metal smelting, scrap metal imports have increased both the metal smelting rate in total industrial output and cities’ reliance on metal smelting, which has significantly increased industrial wastewater discharge in China. Finally, the robustness test demonstrates that increasing metal waste imports will significantly increase the discharge of pollutants by Chinese industrial enterprises, thereby increasing their pollution fees. Specifically, the results of the Ordinary Least Square and IV 2SLS model indicate that if scrap metal imports increase by 1%, industrial enterprises’ pollution fees will significantly increase by 1.081–11.3 million yuan. On the premise of protecting the environment, the Chinese government can import recyclable scrap metal commodities such as high-grade waste copper and aluminium that can meet the product quality standards for enterprises. Additionally, the Chinese government should raise the standards of the metal smelting and recycling industries, reduce the discharge of industrial waste water, and strive to improve the ecological environment.